The Impact of Entrepreneurial Personality and Orientation on SME Innovation in Indonesia: The Role of Centralized Decision-Making, Communication, and Collaboration - Helvyn Angelika; Zunan Setiawan (www.amertainstitute.com, 2024)
This study develops a framework that highlights the individual and collective dimensions of entrepreneurship, emphasizing their combined impact on innovation and performance in small and medium-sized enterprises (SMEs). Using structural equation modeling (SEM) with PLS-SEM 4.0, data from 327 entrepreneurs across major Indonesian cities validate the model’s effectiveness. The research demonstrates that entrepreneurial traits directly foster innovation, underscoring the importance of personal drive and vision. While centralized decision-making correlates with innovation, it significantly impacts communication and collaboration, revealing the complex dynamics between leadership and teamwork in driving innovation. Team communication and collaboration also play crucial roles in enhancing entrepreneurial orientation and collective entrepreneurship, both of which directly improve innovation and business performance. The findings advocate for SMEs to adopt decentralized decision-making and participatory leadership styles to foster innovation. A collaborative, communicative work environment is essential for driving innovation, improving operations, and maintaining competitiveness in a dynamic business landscape. This study provides valuable insights into how individual and collective entrepreneurial efforts shape innovation and performance. It offers practical guidance for entrepreneurs, policymakers, and researchers seeking to strengthen the SME sector through strategies that prioritize innovation and teamwork.